Mental states in caregivers toward people with Alzheimer’s disease at different stages - Li, Bei; Jin, Haiqiang; Yan, Guiying; Zhang, Chen; Chen, Siwei; Wang, Yue; Wang, Ting; Wan, Qiaoqin; Wei, Zhimin; Sun, Yongan (Frontiers in Neurology, 2024)
Caring for people with Alzheimer's disease (AD) is burdensome, especially when family members act as caregivers. This multicenter survey first aimed to investigate caregivers' mental states as well as its influencing factors in caring for people with different severities of AD in China.People with AD and their caregivers from 30 provincial regions in mainland China were enrolled from October 2020 to December 2020 to be surveyed for caregivers' mental states and living conditions, as well as caregivers' attitudes toward treatment and caring. Logistic regression was used to explore the factors that influence the positive and negative states of caregivers who care for people with different stages of AD.Results: A total of 1,966 valid questionnaires were analyzed (mild AD: 795, moderate AD: 521, severe AD: 650). A total of 73.6% of caregivers maintained normal states (mild group: 71.9%, moderate group: 73.9%, severe group: 75.2%; X 2 = 2.023, p = 0.364), and the proportions of caregivers with positive and negative states were 26.3% (mild group: 38.4%, moderate group: 24.6%, severe group: 13.1%; X 2 = 119.000, p< 0.001) and 36.5% (mild group: 25.2%, moderate group: 36.9%, severe group: 50.2%; X 2 = 96.417, p< 0.001), respectively. The major factors that both influenced caregivers' positive and negative states were the severity of AD, perceived efficacy of treatment, safety issues after AD dementia diagnosis and perceived social support (p< 0.005), while neuropsychiatric symptoms causing stress in caregivers (p< 0.001) only affected the negative states of caregivers. The results of further analysis according to disease severity showed that safety issues after AD dementia diagnosis (p < 0.005) only made significant differences in the mild-to-moderate group.To reduce negative states and promote positive states among caregivers, flexible and sensitive caregiving support could be built on caregivers' demands in caring for people with different stages of AD. The support of emotion, social functioning and nursing skills is one of the significant ways for health workers to enhance caregivers' competency.